A SDN-Based Energy Saving Strategy in Wireless Access Networks - Peng, Hongyu; Wang, Weidong; Wang, Chaowei; Chen, Gang; Zhang, Yinghai (China communications, 2015)
This paper investigates on the base stations （BSs） sleeping control and energy saving in wireless network. The objective is to find the sleeping control and energy saving configuration between total power consumption and average video＇s quality. On the Software Defined Network （SDN） access network architecture, a type of sleeping control and active BSs＇ optimal transmitting time strategy is considered, the BS sleeps when there is no active users, and wakes up after a period of vacation time. In this paper, we study the active users grouping strategy, In order to spare more BSs into sleeping mode. Then this paper proposes an active BS transmitting time optimal strategy according to the users＇ QoS. In the proposed strategy, the active BSs＇ transmitting time is minimized in order to save energy. This paper employs the mixed integer-programming model to present this optimization problem. Then we utilized a novel algorithm to save the energy in access networks and also meet the QoS requirements. Both the analytical and simulation results show that the algorithm can effectively save energy in the access network BSs.